The combating revenge porn and the criminal protection of images in Brazil (Revista do Tribunal Regional Federal da 3ª Região, 2020)
This article analyses the need for protection of the image by criminal law. It emphasizes that the defense of the image by the criminal law is a subject that passes for the understanding of the theory of the legal good as instrument for limitation of the criminal intervention. It presents reflections on the importance of consent, expressed or presumed, with regard to the atypicality or the exclusion of illegality of conduct involving the right to image. After a general analysis of the legitimacy and necessity of criminal protection, the text studies the norms of Brazilian law that offer, even if indirectly, protection to the image, as is the case of the Statute of the Child and Adolescent, the Carolina Dieckmann Law and the Law of Protection of People with Special Needs. Finally, the crimes of unauthorized registration of sexual intimacy and dissemination of the scene of rape, sex, nudity or pornography are analyzed.
Keywords: criminal protection of the image; right to privacy; personality rights; porn revenge